Live A/V in Australia - Cooke, Grayson (UTS ePRESS, 2013)
Live AV in Australia by Grayson Cooke documents the diverse emerging national community of practice involved in live audiovisual performance. In a series of video interviews with practitioners around the country a picture emerges of a vibrant performance scene that draws on the aesthetic traditions of music, cinema and new media art.